Factors Affecting Consumers’ Perception on Electronic Payments in the Kathmandu Valley - Maharjan, Aryan; Rawat, Ramesh (Nepalese Journal of Finance, 2025)
This study examines the factors affecting consumers’ perception on electronic payments in the Kath mandu Valley. Consumers’ perception is the dependent variable. The independent variables are ease of use, security, trust, self- efficacy and reliability. The study is based on primary data with 130 respondents. To achieve the purpose of the study structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and factors affecting consumers’ perception on electronic payments in the Kathmandu Valley. The study showed that ease of use has a positive impact on consumers’ perception. It indicates that in crease in ease of use leads to better consumers’ perception. Similarly, security has a positive impact on consumers’ perception. It means that increase in security on electronic payments leads to increase in the better consumers’ perception. Moreover, trust has a positive impact on consumers’ perception. It indicates that better the trust, better would-be consumers’ perception. In addition, self-efficacy has a positive impact in consumers’ perception. It reveals that higher the self-efficacy, better would be the consumers’ perception. Likewise, reliability also has a positive impact in consumers’ perception. It reveals that higher the reliability, better would be the consumers’ perception.